2021
DOI: 10.5114/jcb.2021.112113
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of dosimetric impact of inter-application and intra-application variations in fractionated high-dose-rate intra-cavitary brachytherapy of cervical cancer

Abstract: Purpose: To evaluate feasibility and safety of execution of optimized intra-cavitary brachytherapy (ICBT) plan of first fraction in subsequent fractions in high-volume, low-resource centers.Material and methods: This non-randomized prospective study included 30 cervical cancer patients, who underwent 4 fractions of high-dose-rate (HDR)-ICBT in 2 applications, one week apart, 2 fractions per application delivered on two consecutive days. Computed tomography (CT) simulation was done before each fraction, organs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…OARs (e.g., sigma) typically change position and need re-delineation. Previous studies have suggested that execution of a dose-optimized previous day plan of brachytherapy in subsequent fraction, resulted in an increase of D 2cc doses to OARs [ 28 , 29 ]. Therefore, the work of a medical physicist is required for image fusion, verifying the position of the applicator, and correcting the dose optimization.…”
Section: Discussionmentioning
confidence: 99%
“…OARs (e.g., sigma) typically change position and need re-delineation. Previous studies have suggested that execution of a dose-optimized previous day plan of brachytherapy in subsequent fraction, resulted in an increase of D 2cc doses to OARs [ 28 , 29 ]. Therefore, the work of a medical physicist is required for image fusion, verifying the position of the applicator, and correcting the dose optimization.…”
Section: Discussionmentioning
confidence: 99%